Population Density Levels Wight and Length of Maggot Black Soldier Flies (Hermetia Illucens) with Different Feed Formulation - Khaerunnisa, Salma; Hidayati, Yuli Astuti; Harlia, Ellin (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
Black Soldier Fly (BSF) maggots are decomposing agents cultivated to convert organic materials. Both on-farm and off-farm livestock waste, as well as kitchen organic waste, are organic materials. Organic waste and its by-products can be degraded by BSF maggots into biomass rich in protein, which can be used as feed. This study aims to evaluate the effects of formulating dairy cow feces, milk sediment, and kitchen organic waste (KOW) as growth media on the population density, weight, and length of BSF maggots. The research method used is experimental with a Completely Randomized Design (CRD) involving four treatments and five replicates. The treatments include 100% KOW (P0), 50% KOW and 50% dairy cow feces (P1), 50% KOW and 50% milk sediment (P2), and 33.33% KOW, 33.33% dairy cow feces, and 33.33% milk sediment (P3). BSF maggot rearing was carried out for 20 days, from BSF eggs to the prepupa stage. The conclusion of this study was that the P2 formulation (dairy cow feces and kitchen organic waste) could increase the population density of BSF maggots, and the P3 formulation (dairy cow feces, milk sediment, and kitchen organic waste) could increase the weight and length of BSF maggots.